1995
DOI: 10.1172/jci118074
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide decreases cytokine-induced endothelial activation. Nitric oxide selectively reduces endothelial expression of adhesion molecules and proinflammatory cytokines.

Abstract: IntroductionTo Invest. 1995. 96:60-68.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
852
8
27

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,617 publications
(939 citation statements)
references
References 42 publications
34
852
8
27
Order By: Relevance
“…It has been described that nitric oxide (NO), which is produced as a result of VEGFR-2 signaling, 42 represses gene transcription of VCAM-1 in human saphenous vein endothelial cells. 43 This observation suggests that sunitinib may promote endothelial expression of VCAM-1 by inhibiting the repressing function of NO. In contrast, it has been suggested that the NO-dependent pathway is not involved in VEGF-induced mRNA expression of VCAM-1 in human umbilical vein endothelial cells (HUVECS).…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that nitric oxide (NO), which is produced as a result of VEGFR-2 signaling, 42 represses gene transcription of VCAM-1 in human saphenous vein endothelial cells. 43 This observation suggests that sunitinib may promote endothelial expression of VCAM-1 by inhibiting the repressing function of NO. In contrast, it has been suggested that the NO-dependent pathway is not involved in VEGF-induced mRNA expression of VCAM-1 in human umbilical vein endothelial cells (HUVECS).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of endothelial-derived NO activity leading to reduction in intracellular cGMP levels contributes to impaired vascular responses (Liao et al, 1991), enhanced platelet aggregation (Radomski et al, 1992), and vascular smooth muscle proliferation (Garg and Hassid, 1989). Inhibition of endothelial NO production by the eNOS inhibitor N o -monomethyl-L-arginine (L-NMA) causes vasoconstriction (Kurose et al, 1993), and vascular inflammation by promoting endothelial-leukocyte adhesion (De Caterina et al, 1995). Indeed, lower vascular cGMP levels in mutant mice lacking eNOS are associated with systemic and pulmonary hypertension (Huang et al, 1995;Steudel et al, 1997), greater propensity for intimal smooth muscle proliferation in response to vascular cuff injury (Moroi et al, 1998), and larger stroke sizes in response to cerebral ischemia (Huang et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms are mainly calcium-independent [20] and involve posttranslational modification by phosphorylation of eNOS at regulatory sites [21], messenger RNA (mRNA) stabilization [22], e.g., through heat shock protein 90 (hsp-90), and translocation [23]. NO produced in response to shear stress triggers vascular smooth muscle relaxation, inhibition of apoptosis [24], and inhibition of thrombocyte or monocyte adhesion [25]. Repeated transient shear stress induces NOS3 (eNOS gene) transcription and leads thus to chronically higher NO production in response to stimuli.…”
Section: Introductionmentioning
confidence: 99%